2015
DOI: 10.5152/anatoljcardiol.2015.6483
|View full text |Cite
|
Sign up to set email alerts
|

SYNTAX score predicts postoperative atrial fibrillation in patients undergoing on-pump isolated coronary artery bypass grafting surgery

Abstract: Objective:Atrial fibrillation (AF) is the most common arrhythmia following coronary artery by-pass graft surgery (CABG). The value of SYNTAX score to predict postoperative atrial fibrillation (PoAF) has not been clearly addressed. We aimed to evaluate this relationship in patients undergoing isolated CABG.Methods:This study was designed as a single-center, non-randomized, observational, prospective study. Ninety-four patients undergoing isolated on-pump CABG, who had sinus rhythm and were older than 18 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 36 publications
(35 reference statements)
1
38
4
Order By: Relevance
“…Cerit et al [14] found that age was significantly associated with development of PoAF following CABG in univariate logistic regression analysis. In another study, Geçmen et al [15] showed that age was as an independent variable predicting the development of PoAF in both univariate and multivariate logistic regression analyses. It was found in two different studies that search the relationship between vitamin D and AF in patients undergoing CABG that age was not significantly associated with development of PoAF following CABG [16,17] .…”
Section: Discussionmentioning
confidence: 96%
“…Cerit et al [14] found that age was significantly associated with development of PoAF following CABG in univariate logistic regression analysis. In another study, Geçmen et al [15] showed that age was as an independent variable predicting the development of PoAF in both univariate and multivariate logistic regression analyses. It was found in two different studies that search the relationship between vitamin D and AF in patients undergoing CABG that age was not significantly associated with development of PoAF following CABG [16,17] .…”
Section: Discussionmentioning
confidence: 96%
“…[32] Mendes et al [33] reported that angiographic evidence of right coronary artery stenosis was a predictor of PoAF. Gecmen et al [34] also found that higher SYNTAX scores were related to more frequent PoAF in patients undergoing isolated on-pump CABG. Contrary to this finding, Fukui et al [35] found no significant difference between high and low SYNTAX score groups for the development of PoAF in patients undergoing off-pump CABG.…”
Section: Discussionmentioning
confidence: 92%
“…9,15 No attempts have been made to create a prediction model for POAF after abdominal surgery exclusively; one model has included patients undergoing abdominal surgery, 15 and several models have included patients undergoing cardiac surgery. [10][11][12] A prediction model for patients undergoing abdominal surgery should consider the following clinical data: age, gender, congestive heart failure, renal function (chronic renal disease), pulmonary function (chronic obstructive pulmonary disease) and surgical attributes (eg, emergency vs elective, laparotomy vs laparoscopy, duration of surgery and organ system). Furthermore, addition of paraclinical data of left atrial (LA) size, PR-interval and QRS-duration have improved earlier risk-prediction models and should be considered.…”
Section: Clinical Risk-factors and Prediction Modelsmentioning
confidence: 99%
“…Furthermore, addition of paraclinical data of left atrial (LA) size, PR-interval and QRS-duration have improved earlier risk-prediction models and should be considered. [10][11][12] Blood Plasma Biomarkers Inflammation biomarkers were investigated in one abdominal surgical study and were not found to be associated with POAF. 16 In non-cardiac thoracic surgery, similar conclusions were reached regarding both CRP and IL-6.…”
Section: Clinical Risk-factors and Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation